QUALITY CONTROL ASSAY OF TWO ANTIHYPERTENSIVE REPRESENTATIVES USING RP-HPLC BASED METHODOLOGY: STRESS ASSESSMENT ON ANTIHYPERTENSIVE REPRESENTATIVES - SANTOSH KUMAR, GANDHI; MANDAL, BADAL KUMAR (International Journal of Applied Pharmaceutics, 2022)
Objective: A quick simultaneous separation and quality control assay of two antihypertensive representatives, Azilsartan (AZIL) and Cilnidipine (CLIN) in bulk and tablet formulation was developed and validated using a Reverse phase (RP) HPLC method within a run time of 10 min. Methods: All chromatographic separations of AZIL and CILN were operated on a “Supelco C18 column (250 × 4.6 mm, 5 μ)”, using a mobile phase of Na2SO4 (0.1 M, pH 4.0): methanol at 60:40 (v: v) ratio and the samples were analyzed at 239 nm. Stability assessments of AZIL and CILN were carried out as per the ICH Q1A (R2) regulation. The methodology for determining AZIL and CILN in bulk and formulations tablets was verified by adhering to International Conference on Harmonization (ICH) recommendations. Results: Retention times of AZIL and CILN samples were 4.023 and 5.732 min, respectively, indicating a quick elution time. Over the tested range of 20–60 µg/ml for AZIL and 5–15 µg/ml for CILN determination, calibration curves have displayed linearity and satisfactory results. LOD of AZIL and CILN are 0.083 µg/ml and 0.056 µg/ml, respectively. The approach suggested herein has satisfactory precision (RSD: 0.1013% for AZIL and 0.4944% for CILN) and accuracy (recovery: 99.20 to 100.34 % for AZIL and 100.17 to 101.59 % for CILN). Furthermore, the approach has also been shown to be effective in detecting degradants of AZIL and CILN and resolving them with high resolution. Conclusion: This approach is shown to be acceptable for the accurate quality control assay of two antihypertensive representatives, AZIL and CLIN in both bulk and tablet formulation.